Investigation of Coenzyme A levels in Plasmodium falciparum to ascertain the mode of action of new antimalarial candidates - Scheepers, Melisse Sharne (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.